2019
DOI: 10.3847/1538-4357/aafaff
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Kinematics in a Massive Filamentary Infrared Dark Cloud

Abstract: To probe the initial conditions for high-mass star and cluster formation, we investigate the properties of dense filaments within the infrared dark cloud G035.39-00.33 (IRDC G035.39) in a combined Very Large Array (VLA) and the Green Bank Telescope (GBT) mosaic tracing the NH 3 (1,1) and (2,2) emission down to 0.08 pc scales. Using agglomerative hierarchical clustering on multiple line-of-sight velocity component fitting results, we identify seven extended velocitycoherent components in our data, likely repres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…43,44 The structure and dynamics of G035.39-00.33 have been studied extensively, revealing the presence of multiple sub-filaments which feed their embedded core population. 17,26,[45][46][47][48] Central Molecular Zone (CMZ)…”
Section: Ngc 4321mentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 The structure and dynamics of G035.39-00.33 have been studied extensively, revealing the presence of multiple sub-filaments which feed their embedded core population. 17,26,[45][46][47][48] Central Molecular Zone (CMZ)…”
Section: Ngc 4321mentioning
confidence: 99%
“…Bottom-up approaches involve the decomposition of individual spectra independently from one another. 12,48,83,92,93 With this approach, additional steps must be taken to ensure (physicallymotivated) continuity between adjacent pixels. The top-down methodology involves modelling spatially averaged (and thereby degraded spatial resolution) data, and applying these solutions to the native resolution data.…”
Section: Supplementary Information An Introduction To Spectral Decompmentioning
confidence: 99%
“…Later studies of the kinematic structure of the cloud (Jiménez-Serra et al 2014) have suggested that this may be the result of the merging of several pre-existing molecular filaments at larger scales (Henshaw et al 2013). Such a scenario has been supported by further studies of the kinematics and chemical properties of the cloud (Bisbas et al 2018, Liu et al 2018, Juvela et al 2018, Sokolov et al 2019.…”
Section: Introductionmentioning
confidence: 76%
“…Indeed most of the young stars and cores in low-mass star forming regions are embedded in filaments of gas and dust which dominate the cloud structure (e.g., Schneider & Elmegreen 1979;Ungerechts & Thaddeus 1987;Goldsmith et al 2008), a characteristic shown to be ubiquitous by the large scale maps of the Herschel Space Observatory and Planck satellites (e.g., Molinari et al 2010;André et al 2010André et al , 2014Zari et al 2016). Some of the most prominent cloud filaments actually are collections of velocity-coherent fibers that can become gravitationally unstable and fragment into chains of cores (Hacar et al 2013(Hacar et al , 2017Tafalla & Hacar 2015;Henshaw et al 2016Henshaw et al , 2017Sokolov et al 2019Sokolov et al , 2020Chen et al 2020). However, the exact process ruling the formation of these filamentary structures and their specific role in triggering star E-mail: marta.desimone@univ-grenoble-alpes.fr formation are still debated (e.g., Hennebelle & Inutsuka 2019;Robitaille et al 2020).…”
Section: Introductionmentioning
confidence: 99%